2019
DOI: 10.1093/mnras/stz2149
|View full text |Cite
|
Sign up to set email alerts
|

The clustering of typical Ly α emitters from z ∼ 2.5–6: host halo masses depend on Ly α and UV luminosities

Abstract: We investigate the clustering and halo properties of ∼ 5000 Lyα-selected emission line galaxies (LAEs) from the Slicing COSMOS 4K (SC4K) and from archival NB497 imaging of SA22 split in 15 discrete redshift slices between z ∼ 2.5 − 6. We measure clustering lengths of r 0 ∼ 3 − 6 h −1 Mpc and typical halo masses of ∼ 10 11 M for our narrowband-selected LAEs with typical L Lyα ∼ 10 42−43 erg s −1 . The intermediate band-selected LAEs are observed to have r 0 ∼ 3.5 − 15 h −1 Mpc with typical halo masses of ∼ 10 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 132 publications
(325 reference statements)
12
36
0
Order By: Relevance
“…Assuming that the auto-correlation functions of QSOs and galaxies are both power-laws with the same slope, the relation r 0,QG = (r 0,QQ × r 0,GG ) 1/2 holds, where r 0,QQ and r 0,GG are the auto-correlation lengths of QSOs and galaxies, respectively. As r 0,GG ≈ 20−30 cMpc for galaxies at z ∼ 6 with M UV and a star formation rate (SFR) similar to ours (Khostovan et al 2019), we estimate that r 0,QQ is at least ∼20 cMpc. Such a large correlation length at z ∼ 6 in turn suggests that J1030 is hosted by a dark matter halo with a mass, M h > 10 12 M (Harikane et al 2018;Khostovan et al 2019).…”
Section: Overdensity Levelsupporting
confidence: 81%
See 1 more Smart Citation
“…Assuming that the auto-correlation functions of QSOs and galaxies are both power-laws with the same slope, the relation r 0,QG = (r 0,QQ × r 0,GG ) 1/2 holds, where r 0,QQ and r 0,GG are the auto-correlation lengths of QSOs and galaxies, respectively. As r 0,GG ≈ 20−30 cMpc for galaxies at z ∼ 6 with M UV and a star formation rate (SFR) similar to ours (Khostovan et al 2019), we estimate that r 0,QQ is at least ∼20 cMpc. Such a large correlation length at z ∼ 6 in turn suggests that J1030 is hosted by a dark matter halo with a mass, M h > 10 12 M (Harikane et al 2018;Khostovan et al 2019).…”
Section: Overdensity Levelsupporting
confidence: 81%
“…As r 0,GG ≈ 20−30 cMpc for galaxies at z ∼ 6 with M UV and a star formation rate (SFR) similar to ours (Khostovan et al 2019), we estimate that r 0,QQ is at least ∼20 cMpc. Such a large correlation length at z ∼ 6 in turn suggests that J1030 is hosted by a dark matter halo with a mass, M h > 10 12 M (Harikane et al 2018;Khostovan et al 2019).…”
Section: Overdensity Levelsupporting
confidence: 81%
“…Meurs & Wilson 1984). (2007) and Yamada et al (2012) found bright LAEs around dense regions of the Universe for 2 < z < 5.2 (see also Overzier 2016;Kubo et al 2013). Furthermore, more recently, Khostovan et al (2019) conducted a detailed clustering analysis of faint to luminous LAEs, including the SC4K LAEs, to find that luminous LAEs reside in the most massive dark matter haloes at high redshift, and are therefore consistent with being progenitors of some of the most massive clusters found today (see also Matsuda et al 2004).…”
Section: Agn Age/environment Densitymentioning
confidence: 97%
“…We refer to Sobral et al (2018a) for the full selection criteria and further details regarding the SC4K LAEs. Further information regarding the rest-frame UV morphologies and sizes of SC4K LAEs can be found in Paulino-Afonso et al (2018) and Shibuya et al (2019), while the clustering properties of LAEs and their dependencies on Lyα and SFRs have been extensively studied by Khostovan et al (2019). Figure 1 shows the on-sky distribution of SC4K LAEs in the COSMOS field.…”
Section: Data and Samplementioning
confidence: 99%
“…The spectral properties of LAEs are usually interpreted as to be coming from young ( 50 Myr) and low-mass (M * < 10 10 M ) galaxies (e.g., Wilkins et al 2011;Amorín et al 2017;Hao et al 2018;Santos et al 2020) with small rest-frame UV half-light radii ( R 1 − 2 Kpc, as in e.g., Møller & Warren 1998;Lai et al 2008;Bond et al 2012;Guaita et al 2015;Kobayashi et al 2016;Ribeiro et al 2016;Bouwens et al 2017a;Paulino-Afonso et al 2018) which are actively star-forming (SFR ∼ 1 − 100 M /yr) and dust-poor (dust attenuation A V < 0.2, see e.g., Gawiser et al 2006Gawiser et al , 2007Guaita et al 2011;Nilsson et al 2011;Bouwens et al 2017b;Arrabal Haro et al 2020). When observed at high redshift, isolated and grouped LAEs would represent the progenitors of present-day galaxies and clusters, respectively, hence providing extremely valuable insights about structure formation (e.g., Matsuda et al 2004Matsuda et al , 2005Venemans et al 2005;Gawiser et al 2007;Overzier et al 2008;Guaita et al 2010;Mei et al 2015;Bouwens et al 2017b; Khostovan et al 2019). A basic statistical tool to study the population of high-z LAEs is the description of their number density, at a given redshift, as a function of line luminosity (L Lyα ), namely the Lyα luminosity function (LF, see e.g., Gronke et al The measured transmission curves for the J-PLUS filter set, after accounting for sky absorption, CCD quantum efficiency and the total effect of the JAST/T80 telescope optical system.…”
Section: Introductionmentioning
confidence: 99%